East Asia Update, November 2006 : Managing Through a Global Downturn - World Bank (World Bank, Washington, DC, 2020)
Growth in Emerging East Asia is expected to reach close to 8 percent in 2006, the second strongest pace in the five year long economic expansion underway in the region since 2001. Emerging East Asia comprises Developing East Asia (China, Indonesia, Malaysia, Philippines, Thailand, Vietnam and some smaller economies) and four Newly Industrialized Economies or NIEs (Hong Kong, Korea, Singapore and Taiwan, China). The rest of this summary provides further information on the main cross-country trends and policy issues discussed in this report. Developments at the country level are discussed in the Country Sections at the back of the report, while fuller Country Briefs are available at the website associated with this report. The Special Focus in this report is on Investing in Young People in East Asia and the Pacific, a study of the lessons for East Asia from the World Bank's recent World Development Report 2007: Development and the Next Generation.